Pengaruh Kemiskinan Terhadap Pertumbuhan Ekonomi di Provinsi Banten - Wirantara, Syahtriandi; Ramdani, Risa Novianti; Mauralifta, Yuan Amelia; Handayani, Noviarti Elsa (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2024)
Poverty is a real problem in many regions, including in Banten. Poverty has a very broad impact, including its negative impact on economic growth. This study aims to identify the effect of poverty on economic growth by using secondary data from various sources such as BPS, and Related Literature. The result is that there is a negative relationship between the level of poverty and economic growth. Poverty can hinder economic growth through a variety of channels, including reduced labor productivity, decreased purchasing power, and lack of access to education. Therefore, efforts to reduce poverty are expected to support sustainable economic growth. This study is intended to contribute to broaden horizons related to the relationship between poverty and economic growth and provide relevant policy implications to address the problem of poverty and increase economic growth in Indonesia, especially in Banten province.